Fundamentals of food engineering - Rao, D. G. [ (Dubasi Govardhana)] (New Delhi, India : PHI Learning, 2010)
Food technology is the application of food science to the selection, preservation, processing, packaging, distribution and use of safe nutritious and wholesome food
1. General introduction -- 2. Basic engineering principles -- 3. Unit operations -- 4. Food industry management
Includes index
Keywords: Food engineering; Food industry and trade; Food industry management; Material handling and transportation; Refrigeration; Thermodynamics